An ontology to represent energy-related occupant behavior in buildings. Part II: Implementation of the DNAS framework using an XML schema. (December 2015) - Hong, Tianzhen; D'Oca, Simona; Taylor-Lange, Sarah C.; Turner, William J.N.; Chen, Yixing; Corgnati, Stefano P.
Abstract: Energy-related occupant behavior in buildings is difficult to define and quantify, yet critical to our understanding of total building energy consumption. Part I of this two-part paper introduced the DNAS (Drivers, Needs, Actions and Systems) framework, to standardize the description of energy-related occupant behavior in buildings. Part II of this paper implements the DNAS framework into an XML (eXtensible Markup Language) schema, titled 'occupant behavior XML' (obXML). The obXML schema is used for the practical implementation of the DNAS framework into building simulation tools. The topology of the DNAS framework implemented in the obXML schema has a main root element OccupantBehavior, linking three main elements representing Buildings, Occupants and Behaviors . Using the schema structure, the actions of turning on an air conditioner and closing blinds provide two examples of how the schema standardizes these actions using XML. The obXML schema has inherent flexibility to represent numerous, diverse and complex types of occupant behaviors in buildings, and it can also be expanded to encompass new types of behaviors. The implementation of the DNAS framework into the obXML schema will facilitate the development of occupant information modeling (OIM) by providing interoperability between occupant behavior models and building energy modeling programs. Highlights: An occupant behavior XML schema obXML is developed based on the DNAs framework. The obXML provides a standardize representation of occupant behavior in buildings. The obXML is used to describe windows opening and blinds closing behavior as examples. The obXML is generic and flexible for expansion to describe new occupant behavior. The obXML schema is planned to integrate with building information modeling.